An Exploration of Verbal Bullying Types and The Role of Bystanders in Affecting Victims' Mental Health - Sari, Desi Purnama; Mariyani; Miko, Aris Temas; Oktviana, Annisa (Tell : Teaching of English Language and Literature Journal, 2024)
This study aims to explore the prevalence and impact of verbal bullying among adolescents, as well as the role of bystanders in these situations. The methodology involved a survey of 93 respondents, with mental health assessment conducted using the Self-Reporting Questionnaire (SRQ) validated by the WHO, which is a reliable tool for measuring mental health in adolescent populations. The findings show that 39.8% of respondents experienced verbal bullying, primarily in the form of hurtful words (57.8%) and name-calling (42.2%), mostly perpetrated by peers (60.2%). Additionally, 44.6% of respondents reported the presence of bystanders during these incidents, with most (51.4%) attempting to help the victims, although a substantial proportion (43.2%) chose to remain silent, reflecting the complex dynamics in bullying situations. Verbal bullying has significant effects on individuals' mental health, as evidenced by 64.9% of respondents reporting mental health issues related to verbal bullying. Furthermore, interviews with 9 selected victims revealed a range of emotions based on bystander behavior, highlighting feelings of anger, sadness, and anxiety when bystanders supported the perpetrator or remained passive, while victims felt relief and gratitude when defended. Importantly, the perspective of bystanders was not examined in this study. While the research focused on the experiences of victims of verbal bullying and the emotional impacts they face, it did not delve into the motivations, feelings, or actions of bystanders. Understanding how bystanders perceive bullying situations and what influences their decisions could provide a more comprehensive view of the dynamics involved in bullying. Future studies could explore these aspects to gain insights into the bystander effect and its implications for both victims and witnesses.